THE USE OF DRIP-WATER IRRIGATION SYSTEM AND ITS EFFECTIVENESS IN INCREASING THE PRODUCTIVITY OF THE AGRI-HOLTICULTURAL SOCIETY IN DESA HAMPARAN PERAK - Thohiri, Roza; Sagala, Gaffar Hafiz; Zainal, Andri (Universitas Negeri Medan, 2018)
AbstractAlthough the developments of technology has been grown rapidly, some farmers in North Sumatra are still trapped in traditional farming methods. The problem of limited funds has always been a classical reason for explaining the stagnancy. Interestingly, the farmer community of Hamparan Perak, North Sumatra, which is a partner of LPM UNIMED, actually has advanced knowledge in the management of horticultural crops. Simple innovation seem to be able to drive farm productivity and efficiency. The general purpose of this community service activity is to implement the drip-water irrigation system at Agro-Holticulture plantation of Hamparan Perak Farmer Community in Hamparan Perak, Deli Serdang, North Sumatera. In particular, this community service aims to: 1) improving the efficiency of agricultural production with the implementation of such technology; and 2) increasing farm productivity with improved irrigation system. This Community Service Activities using technical guidance methods to farmer community. Furthermore, efficiency and productivity are met through minimizing costs and increasing farmer income which observed during technical guidance. Based on ongoing observations, farmers acknowledge that the process of agricultural production becomes very efficient while the performance of the crops becomes more productive.Keywords: Farmers, Horticulture, Efficiency, Productivity